The Role of Public Relations in Promoting the Educational Community Via Instagram @Aksararembaka - Farah Dalilah Balqis; Nurhanifah Nurhanifah; Almaidah Siregar; Indah Ardianti; Ahlan Adib Albarry (Education Achievement: Journal of Science and Research, 2024)
The purpose of this research is to find out what strategies are used in promoting the community and what obstacles usually occur when promoting on Instagram. This study uses a qualitative method by conducting interviews with the founder of Aksara Rembaka. In this study, the results obtained are that the strategies used to promote vary greatly, including providing creative content and conducting various collaborations and the obstacles that usually occur are unstable Instagram algorithms and resources, both human and financial, so that public relations are very influential for the success of a community to be recognized.